2018
DOI: 10.1016/j.cjca.2018.08.026
|View full text |Cite
|
Sign up to set email alerts
|

2018 Focused Update of the Canadian Cardiovascular Society Guidelines for the Management of Atrial Fibrillation

Abstract: The Canadian Cardiovascular Society (CCS) Atrial Fibrillation Guidelines Committee provides periodic reviews of new data to produce focused updates that address clinically important advances in atrial fibrillation (AF) management. This 2018 Focused Update addresses: (1) anticoagulation in the context of cardioversion of AF; (2) the management of antithrombotic therapy for patients with AF in the context of coronary artery disease; (3) investigation and management of subclinical AF; (4) the use of antidotes for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
201
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 210 publications
(212 citation statements)
references
References 162 publications
(212 reference statements)
4
201
0
7
Order By: Relevance
“…The higher TATT prescription rate is in agreement with the CCS 2016 AF guidelines recommendation of TATT for 3 to 6 months in these patients with CHADS2 score ≥ 2, placing greater weight on reduction of thromboembolic events and comparatively lesser weight on risk of major bleeding . A course of TATT of a duration of up to 6 months in patients at high risk of thrombosis was also advocated subsequently in the 2018 update of the CCS antiplatelet guidelines . The emergence of dual pathway antithrombotic therapy (anticoagulant plus a single antiplatelet agent) in clinical practice, on the other hand, represents an integration of randomized trial data from PIONEER AF‐PCI (rivaroxaban) and REDUAL (dabigatran) that showed that such a regimen could minimize bleeding risk without a signal for increase in clinical ischemic events .…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The higher TATT prescription rate is in agreement with the CCS 2016 AF guidelines recommendation of TATT for 3 to 6 months in these patients with CHADS2 score ≥ 2, placing greater weight on reduction of thromboembolic events and comparatively lesser weight on risk of major bleeding . A course of TATT of a duration of up to 6 months in patients at high risk of thrombosis was also advocated subsequently in the 2018 update of the CCS antiplatelet guidelines . The emergence of dual pathway antithrombotic therapy (anticoagulant plus a single antiplatelet agent) in clinical practice, on the other hand, represents an integration of randomized trial data from PIONEER AF‐PCI (rivaroxaban) and REDUAL (dabigatran) that showed that such a regimen could minimize bleeding risk without a signal for increase in clinical ischemic events .…”
Section: Discussionsupporting
confidence: 60%
“…10,11 A shift to dual pathway antithrombotic management is also advocated in the 2018 updates of the CCS antiplatelet and atrial fibrillation guidelines. 16,17 The recently published AUGUSTUS trial (apixaban), that also included medically managed ACS patients, also supports the safety advantage of dual pathway therapy over triple therapy. 12 The ENTRUST-PCI AF trial (edoxaban) furtherly reinforced the safety and anti-ischemic efficacy of dual pathway regimens of dual pathway over triple therapy, with no significant difference in ischemic events between the two groups.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…We read with interest the commentary of Stiell et al 1 regarding the 2018 Canadian Cardiovascular Society (CCS) Atrial Fibrillation (AF) guidelines. 2 While we recognise that these guidelines present challenges to emergency physicians, they are supported by the evidence. 3 Stiell et al appear most concerned regarding the recommendation for four weeks of oral anticoagulation therapy following cardioversion of atrial fibrillation, even for episodes <48 hours in duration and in patients without thromboembolic risk factors.…”
mentioning
confidence: 98%